The Legal protection for the electronic consumer in the Algerian Legislation - Mohammed ELFODDA; Tahar Nouacer (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
In light of the growth of contracts concluded through electronic means, the danger and threat of the consumer in the face of the professional has grown.